The management of displaced humeral shaft fractures – A survey of UK shoulder and elbow surgeons. (June 2022) - Ahad, Abdul; Haque, Aziz; Armstrong, Alison; Modi, Amit; Pandey, Radhakant; Singh, Harvinder Pal
Introduction: Indications for surgical management of displaced humeral shaft fractures are not clearly established, leading to variations in practice. The aim of this study was to determine the scale of these variations in the UK practice to help design a future national trial. Methods: An online survey was sent to all surgeon members of British Elbow and Shoulder Society to help define humeral shaft fractures, fracture displacement as well as indications for operative and non-operative management. Patient and injury related factors considered important when managing humeral shaft fractures were investigated. Results: The survey achieved a response rate of 32% (104/327). There was a lack of consensus on definitions for humeral shaft fractures and fracture displacement. A functional brace was the most common form of non-operative treatment (63%). Majority immobilise humeral shaft fractures for 4–8 weeks or until callus are visible (62%) with a similar number considering operative treatment if adequate signs of healing are not present at around 12–16 weeks. Around half of our respondents exclusively use plates with variations in preference of approach and a minority (2%) exclusively use intra-medullary nails. Conclusion: The significant variation in management of displaced humeral shaft fractures in the UK suggests a clear need to evaluate clinical and cost effectiveness through a multi-centre randomised trial.